1995
DOI: 10.1111/j.1365-2796.1995.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of inappropriate secretion of antidiuretic hormone (SIADH) in malignant disease

Abstract: . The first clinical case of a patient with the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) was presented by Schwartz et al. in 1957 (Am J Med 1957; 23: 529–42), describing two patients with lung cancer who developed hypo‐natraemia associated with continued urinary sodium loss. They postulated that the tumours led to the inappropriate release of antidiuretic hormone (ADH), later discovered to consist of arginine‐vasopressin (AVP). This suggestion was later confirmed in several studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
195
1
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(212 citation statements)
references
References 115 publications
5
195
1
5
Order By: Relevance
“…Hyponatremia related to SIADH has been associated with various antineoplastic agents, including vincristine, CY, ifosfamide, and thiotepa. 10,11 However, our analysis showed that drugs and radiation used during conditioning were not associated with SIADH. SIADH has also been reported to be associated with several hematological diseases such as NHL and Hodgkin's disease.…”
Section: Discussionmentioning
confidence: 60%
“…Hyponatremia related to SIADH has been associated with various antineoplastic agents, including vincristine, CY, ifosfamide, and thiotepa. 10,11 However, our analysis showed that drugs and radiation used during conditioning were not associated with SIADH. SIADH has also been reported to be associated with several hematological diseases such as NHL and Hodgkin's disease.…”
Section: Discussionmentioning
confidence: 60%
“…It is estimated that SIADH occurs in 15% of patients with SCLC and in 0.7% of patients with NSCLC. Other neoplasms that coexist with hyponatraemia are first of all carcinomas of the head and neck (3%), primary and metastatic tumours of the CNS, breast carcinoma, haematological malignancies (lymphomas, chronic lymphocytic leukaemia, multiple myeloma) and many others [13]. SIADH is also diagnosed in the course of many nonneoplastic diseases: in CNS diseases (traumas, meningitis, encephalitis, postoperative states), psychoses and benign diseases of the lung and pleura -in pleuritis, pneumonia, tuberculosis, empyema and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…While looking for other causes of hyponatraemia in cancer patients it should be remembered that stress and pain may be important contributing factors [13].…”
Section: Discussionmentioning
confidence: 99%
“…TURP is surgical manipulation which highly risks water intoxication post-surgically. SIADH is common in humans suffering from multiple tumors (Talmi et al, 1992;Sorensen et al, 1995), however evaluation of patient's anamnesis didn't bring out any associated tumor and surgical manipulation. Furthermore, urinanalysis of cat didn't reveal any significant changes as the patients of SIADH are usually characterized by more concentrated and less volume urine (Dibartola, 2012).…”
Section: Discussionmentioning
confidence: 99%